Initiation of sacubitril/valsartan in haemodynamically stabilised heart failure patients in hospital or early after discharge: primary results of the randomised TRANSITION study. (27th May 2019) - Wachter, Rolf; Senni, Michele; Belohlavek, Jan; Straburzynska‐Migaj, Ewa; Witte, Klaus K.; Kobalava, Zhanna; Fonseca, Candida; Goncalvesova, Eva; Cavusoglu, Yuksel; Fernandez, Alberto; Chaaban, Said; Bøhmer, Ellen; et al.
Abstract : Aims: To assess tolerability and optimal time point for initiation of sacubitril/valsartan in patients stabilised after acute heart failure (AHF). Methods and results: TRANSITION was a randomised, multicentre, open‐label study comparing two treatment initiation modalities of sacubitril/valsartan. Patients aged ≥ 18 years, hospitalised for AHF were stratified according to pre‐admission use of renin–angiotensin–aldosterone system inhibitors and randomised ( n  = 1002) after stabilisation to initiate sacubitril/valsartan either ≥ 12‐h pre‐discharge or between Days 1–14 post‐discharge. Starting dose (as per label) was 24/26 mg or 49/51 mg bid with up‐ or down‐titration based on tolerability. The primary endpoint was the proportion of patients attaining 97/103 mg bid target dose after 10 weeks. Median time of first dose of sacubitril/valsartan from the day of discharge was Day –1 and Day +1 in the pre‐discharge group and the post‐discharge group, respectively. Comparable proportions of patients in the pre‐ and post‐discharge initiation groups met the primary endpoint [45.4% vs. 50.7%; risk ratio (RR) 0.90; 95% confidence interval (CI) 0.79–1.02]. The proportion of patients who achieved and maintained for ≥ 2 weeks leading to Week 10, either 49/51 or 97/103 mg bid was 62.1% vs. 68.5% (RR 0.91; 95% CI 0.83–0.99); or any dose was 86.0% vs. 89.6% (RR 0.96; 95% CI 0.92–1.01). Discontinuation due to adverse events occurred in 7.3% vs. 4.9% of patients (RR 1.49; 95% CI 0.90–2.46). Conclusions: Initiation of sacubitril/valsartan in a wide range of heart failure with reduced ejection fraction patients stabilised after an AHF event, either in hospital or shortly after discharge, is feasible with about half of the patients achieving target dose within 10 weeks. Clinical Trial Registration: ClinicalTrials.gov ID: NCT02661217